Throughfall and stemflow are major hydrologic highways for particulate traffic through tree canopies. Issue 7 (3rd June 2021) - Van Stan, John T; Ponette‐González, Alexandra G; Swanson, Travis; Weathers, Kathleen C
Abstract : For one‐third of Earth's land surface, precipitation passes through tree canopies (as throughfall or stemflow) before entering watersheds. Over a century of research has described fluxes of water and solutes along these "hydrologic highways", yet little is known about their "traffic" – that is, the organisms and nonliving particulates frequently discarded from water samples after filtration in the lab. A comprehensive understanding of the composition of sub‐canopy precipitation is necessary to estimate the total nutrient and pollutant inputs to watersheds for redistribution downstream, as well as to systematically investigate precipitation effects on organismal exchanges along the atmosphere–plant–soil continuum. Here, we review current concepts and research showing that the hydrologic highways from tree canopies to soil carry ecologically relevant quantities of biologic (viruses, microbes, microfauna, and meiofauna) and abiotic particulates. Their fate may have important consequences for the biogeochemistry and biodiversity of terrestrial systems.